Molecular and biotechnical approaches for oil quality improvement in Brassica species: Molecular and biotechnical approaches for oil quality improvement in Brassica species - V BLESSY; R P GNANAMALAR; K MANIVELAN (Journal of Oilseeds Research, 2020)
Crop Brassicas encompass many diverse types of plants, which are grown as vegetables, fodder or sources of oils and condiments. Rapeseed-mustard comprising eight different species viz., Indian mustard, toria, yellow sarson, brown sarson, gobhi sarson, karanrai, black mustard and taramira. The oleiferous Brassica species, commonly known as rapeseed-mustard is the major group among the oil seed production in the world and it constitutes the world’s third important source of edible oil. High amount of erucic acid; C22:1 (40-57%), presence of high level of glucosinalates and other phenolic compounds lower its utility as edible oil. The quality improvement emphasis is to reduce/eliminate these compounds. The conversion of erucic to oleic acid is done by fatty acid elongase (FAE1) coding for ß ketoacylCoA synthase (KCS). Omics and GWAS help in dissecting the desired QTLs. Molecular evidence has revealed that two-base-pair deletion of AA at the 1,422–1,423 base sites (eC2) for the FAE1 gene resulted in the low erucic acid (LEA) phenotypes. The C-QTL’s viz., OIL-C-A8-1,OIL-C-A10-1,OIL-C-B1-1,OIL- C-B2-1,OIL-C-B3-1,OIL-C-B4- 1,OIL-C-B7-1 contributed for high oil content. CYP79F1 is involved in regulating the synthesis of 3C Glucosinolates in B. juncea. The RNAi method is the powerful technique in suppressing the activity of FAE1 and helps in down regulating the production of erucic acid and thus contributing for the development of the zero erucic acid lines. There is meager research work in the elimination/reduction of other anti- nutritional factors which has to be improved by the breeding efforts.